Time, Hydrologic Landscape, and the Long‐Term Storage of Peatland Carbon in Sedimentary Basins. Issue 3 (14th March 2021) - Large, David J.; Marshall, Chris; Jochmann, Malte; Jensen, Maria; Spiro, Baruch F.; Olaussen, Snorre
Abstract: Peatland carbon may enter long‐term storage in sedimentary basins preserved as either coal or lignite. The time required to account for the carbon in 1–10 m thick coal seams must represent 10 5 –10 6 years, an order of magnitude more than previously assumed. To understand the process by which this happens requires extrapolation of our understanding of peatland carbon accumulation over timescales that greatly exceed those of Holocene peat. We analyze the consequences of extrapolating peat growth to periods of 10 6 years. We deduce that that key to sustained peat growth are hydrologic landscapes that can maintain a saturated peat body above the level of clastic deposition. Contrary to current stratigraphic frameworks, we conclude that the generation of accommodation space at low rates of 0.1–0.2 mm/yr can adequately accommodate thick peat accumulation over periods >10 5 years. However, generation of accommodation space at rates >0.5 mm/yr cannot. The low rates that permit accommodation of thick peat are typical of the rates of subsidence in specific tectonic settings, particularly foreland basins, and this has implications for our understanding of the links between terrestrial carbon burial, tectonics and the carbon cycle. The long‐term stability of extensive peatland required to form coal also requires sediment bypass, modifying basin wide sediment transport and deposition. Limits to peatland growth under very low accommodation rates must exist but the relative importance of the limiting process is not understood. Finally, we discuss the consequences of these factors for predicting the future of the peatland carbon reservoir. Plain Language Summary: Over the past 300 million years peatland carbon has accumulated in sedimentary rocks where it occurs as coal and lignite. This process is important as it removes carbon dioxide from the atmosphere and stores it as carbon in the Earth's crust, providing a long‐term cooling mechanism for global climate. In this context, recent research has shown that layers of coal previously thought to have accumulated over 10, 000 years have accumulated over periods of a hundred thousand to one million years. This marks a huge shift in our understanding of the periods over which peat can accumulate continuously. In this study, we explore the consequences of this for our understanding of the surface and tectonic processes that lead to the storage of peatland carbon in sedimentary rocks. We show that the key to continuous peat accumulation and crustal storage of carbon are landscapes that maintain stable hydrology with lower rates of subsidence than previously thought. Applying these observations, we provide a new framework for interpreting peat, lignite and coal. We then highlight links between tectonic process and peatland carbon storage, and discuss gaps in our understanding of peatland processes, particularly the limits to peat accumulation within a landscape. Key Points: To understand how peat enters long term carbon storage requires consideration of peat accumulation over periods of 0.1–1 Myr years Peat accumulation over these timeframes requires sustained storage of water above depositional base level This has profound implications for our understanding of peat in the earth system and the interpretation of the geological record